Air Pollution Control and Sustainable Development (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
The following topical collection, entitled "Air Pollution Control and Sustainable Development: Innovative Methods and Policy Implications," focuses on the intersection of innovative methods of air quality management and the pursuit of sustainable development. This topical collection brings together pioneering research that explores how innovative methods, such as advanced data-driven modeling and geographically weighted regression, can inform and shape effective policies for air pollution control. The studies presented span various regions and contexts, from urban form analysis in China's cities to source contribution assessments in the Iberian Peninsula, highlighting the global relevance of these issues. By emphasizing the critical role of policy in driving sustainable solutions, it offers insights into how technological advancements and regulatory frameworks can work together to address the pressing challenges of air pollution. It is an essential resource for those seeking to understand and implement strategies that not only control pollution but also support broader sustainability goals, making significant contributions to the field of environmental management.